Investigating the role of glycoprotein hormone GPA2/GPB5 signaling in reproduction in adult female Rhodnius prolixus - Al-Dailami, Areej N.; Orchard, Ian; Lange, Angela B. (Frontiers in Insect Science, 2022)
Glycoprotein hormones are complex molecules essential for regulating various physiological activities in vertebrates and invertebrates. In vertebrates, the classical glycoprotein hormones include follicle-stimulating hormone (FSH), luteinizing hormone (LH), thyroid-stimulating hormone (TSH) and chorionic gonadotropin (CG), which have crucial roles in growth, development, metabolism, and reproduction. The recently discovered heterodimeric glycoprotein hormone GPA2/GPB5 (called thyrostimulin in vertebrates) is suggested to be involved in reproductive processes in arthropods. Here, we focus on understanding the role of GPA2/GPB5 and its receptor, LGR1, in the reproductive success of female Rhodnius prolixus, a vector of Chagas disease. Both subunit transcripts, GPA2 and GPB5, are present in a variety of tissues, with the greatest expression in the central nervous system, whereas the LGR1 transcript is present in peripheral tissues, including the fat body and the reproductive system of adult females. In the adult female, GPB5-like immunoreactive axonal projections are present in the trunk nerves extending onto the reproductive tissues, with processes overlaying the ovaries, oviducts, spermatheca, and bursa, indicating the possibility of neural control by neurons containing GPA2/GPB5. GPB5-like immunoreactive processes and blebs are also localized to the previtellogenic follicles, suggesting an involvement of this glycoprotein hormone signaling in oocyte development. LGR1 transcript expression increases in the adult female reproductive system post-feeding, a stimulus that initiates reproductive development, adding further support to an involvement in reproduction. We have investigated the effect of LGR1 downregulation on reproductive processes, monitoring the number and the quality of eggs laid, hatching ratio, and production of vitellogenin (Vg), the major yolk protein for developing eggs. Downregulation of LGR1 leads to increases in transcript expression of vitellogenin, RhoprVg1, in the fat body and the vitellogenin receptor, RhoprVgR, in the ovaries. Total protein in the fat body and hemolymph of dsLGR1-injected insects increased compared to controls and associated with this effect was a significant increase in vitellogenin in these tissues. dsLGR1 injection leads to accelerated oogenesis, an increase in the number of eggs produced and laid, an increase in egg size and a reduction in hatching rate. Our results indicate that GPA2/GPB5 signaling acts to delay egg production in adult female R. prolixus.